Adaptive Concurrent Topology Optimization of Coated Structures with Nonperiodic Infill for Additive Manufacturing. (December 2020) - Hoang, Van-Nam; Tran, Phuong; Nguyen, Ngoc-Linh; Hackl, Klaus; Nguyen-Xuan, H.
Abstract: The present research develops a direct multiscale topology optimization method for additive manufacturing (AM) of coated structures with nonperiodic infill by employing an adaptive mapping technique of adaptive geometric components (AGCs). The AGCs consist of a framework of macro-sandwich bars that represent the macrostructure with the solid coating and a network of micro-solid bars that represent the nonperiodic infill at the microstructural scale. The macrostructure including the coating skin and the internal architecture of the microstructures of cellular structures is simultaneously optimized by straightforwardly searching optimal geometries of the AGCs. Compared with most existing methods, the proposed method does not require material homogenization technique at the microscale; the continuity of microstructures and structural porosities are ensured without additional constraints; Finite element analysis (FEA) and geometric parameter updates are required only once for each optimization iteration. AGCs allow us to model coated structures with porosity infill on a coarse finite element mesh. The adaptive mapping technique may reduce mapping time by up to 50%. Besides, it is easy to control the length scales of the coating and infill as desired to make it possible with AM. This investigation also explores the ability to realize concurrent designs of coated structures with nonperiodic infill patterns using 3D printing techniques. Highlights: Explicit topology optimization of coated structures with nonperiodic infill is proposed. The structure, including the macrostructural topology, coating and infill, is simultaneously optimized without material homogenization and connector and local volume constraints. Structural feature sizes are explicitly controlled without filtering techniques or additional constraints. The coated structure with porous infill can be simply designed in a coarse finite element grid. Concurrent designs of coated structures with nonperiodic infill are then realized by using 3D printing techniques.